2009
DOI: 10.1007/s11255-009-9694-y
|View full text |Cite
|
Sign up to set email alerts
|

The association of glomerular filtration rate and erectile dysfunction with severity of coronary artery disease in patients presenting with chest pain

Abstract: The presence and severity of ED and reduced eGFR are associated with the severity of underlying CAD in patients presenting with chest pain, and they could be implemented in the risk stratification of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Adult male patients with ED and chest pain, presumably of coronary origin, had a worse GFR ( 24 ). As the severity of the ED increased, a more severe decrease in the creatinine clearance occurred in male subjects with chest pain ( 25 ). Observational research involving 270 consecutive hypertensive male patients showed a significant correlation between the ED score and GFR ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adult male patients with ED and chest pain, presumably of coronary origin, had a worse GFR ( 24 ). As the severity of the ED increased, a more severe decrease in the creatinine clearance occurred in male subjects with chest pain ( 25 ). Observational research involving 270 consecutive hypertensive male patients showed a significant correlation between the ED score and GFR ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was a cross‐sectional study, and the participants were recruited from a prospectively maintained cohort. Previously we reported that reduced estimated glomerular filtration rate (eGFR), and presence and severity of ED were associated with severity of CAD in this cohort [31]. We included 312 consecutive adult male patients who for the first time presenting with chest pain to our cardiology outpatient clinic.…”
Section: Methodsmentioning
confidence: 99%
“…Clinically and experimentally, accelerated pathogenic vascular adaptations have been linked to a decline in erectile function [13,34,35]. In CKD patients, both the degree of CAD [36] and severity of coronary artery calcification [37] have been associated with ED. While the bilateral internal pudendal artery (IPA) is the dominant controller of total penile vascular resistance (∼70%) [38], its susceptibility to vascular calcification in CKD is not well established.…”
Section: Introductionmentioning
confidence: 99%